PENGARUH POLA ASUH ORANG TUA TERHADAP KEDISIPLINAN ANAK DI PAUD AN NUR MARGOYOSO - Lis Magfiroh; Dewi Yanti; Mansur (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2025)
This research is quantitative research with a causal approach. This study aims to determine The influence of parental parenting on the learning discipline of Paud An Nur Margoyoso. The population of this study was 90 students with a sample size of 47 students. The research results show that the influence of parental parenting on student learning discipline is shown by statistical analysis which produces coefficients correlation (rxy) of 0.53. This shows the influence of parental parenting on student learning discipline, meanwhile coefficient of determination (r2) of 0.28 or 28%. The remaining 72% is determined by other factors. Average learning discipline among students, 28% is determined by parenting patterns through the regression equation Ŷ= 74.26 + 0.41X, meaning that every increase unit value of parental parenting will cause an increase in student learning discipline by 0.41 units. Based on the results of this research It can be concluded that there is a positive influence between parenting patterns on student learning discipline in Paud An Nur Margoyoso.